2021
DOI: 10.1371/journal.pone.0259062
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Serbian COVID Stress Scales

Abstract: This study aimed to generate a linguistic equivalent of the COVID Stress Scales (CSS) in the Serbian language and examine its psychometric characteristics. Data were collected from September to December 2020 among the general population of three cities in Republic of Serbia and Republic of Srpska, countries where the Serbian language is spoken. Participants completed a socio-demographic questionnaire, followed by the CSS and Perceived Stress Scale (PSS). The CSS was validated using the standard methodology (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
(50 reference statements)
2
14
0
Order By: Relevance
“…The means of the scale sums are comparable to other translated versions used in the general population (when means are reported), they are descriptively between, for example, the Swedish version (descriptively slightly lower values) [ 24 ] and the Serbian version (mostly descriptively slightly higher values) [ 23 ]. In the English version [data collection 03-04/2020, 16], values were slightly higher descriptively, whereas it was also shown in a longitudinal design [ 18 ] that CSS values were higher in an earlier phase of the pandemic (03-04/2020) than in a later phase (03-05/2021).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The means of the scale sums are comparable to other translated versions used in the general population (when means are reported), they are descriptively between, for example, the Swedish version (descriptively slightly lower values) [ 24 ] and the Serbian version (mostly descriptively slightly higher values) [ 23 ]. In the English version [data collection 03-04/2020, 16], values were slightly higher descriptively, whereas it was also shown in a longitudinal design [ 18 ] that CSS values were higher in an earlier phase of the pandemic (03-04/2020) than in a later phase (03-05/2021).…”
Section: Discussionmentioning
confidence: 63%
“…In the German version, these subscales showed a high and the highest intercorrelation ( r = .65), so that the German version also confirms their proximity to each other. Nevertheless, the two subscales seem to be sufficiently differentiated from each other [ 24 ] and international studies found in direct comparisons a superiority of the 6-factor solution over the 5-factor solution [ 19 , 23 25 ]. Possible explanations for this slight deviation in factor structure could be due to the dynamic events of the COVID-19 pandemic as well as country-specific incidences and measures (e.g., change in threat due to changes in incidence, increase in knowledge regarding the virus, changes in protective measures).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cronbach’s alpha coefficient of the CSS was 0.932 (n = 36), indicating a very high level of reliability [ 30 ]. The scale was validated and translated into Serbian in 2021 [ 31 ]. COVID-19-related fear was measured by a one-dimensional COVID-19 Fear Scale (FCV-19S) [ 29 ], which uses seven items to assess the gravity of COVID-19-related fear.…”
Section: Methodsmentioning
confidence: 99%
“…The Cronbach’s alpha coefficient of the CSS was 0.932 (n = 36), indicating a very high level of reliability [ 30 ]. The scale was validated and translated into Serbian in 2021 [ 31 ].…”
Section: Methodsmentioning
confidence: 99%